Regional Economic Outlook, April 2017, Sub-Saharan Africa - Allard, Celine (Regional Economic Outlook, 2017)
Growth momentum in sub-Saharan Africa remains fragile, marking a break from the rapid expansion witnessed since the turn of the millennium. 2016 was a difficult year for many countries, with regional growth dipping to 1.4 percent-the lowest level of growth in more than two decades. Most oil exporters were in recession, and conditions in other resource-intensive countries remained difficult. Other nonresource-intensive countries however, continued to grow robustly. A modest recovery in growth of about 2.6 percent is expected in 2017, but this falls short of past trends and is too low to put sub-Saharan Africa back on a path of rising living standards. While sub-Saharan Africa remains a region with tremendous growth potential, the deterioration in the overall outlook partly reflects insufficient policy adjustment. In that context, and to reap this potential, strong and sound domestic policy measures are needed to restart the growth engine.